Justifiable energy injustices? Exploring institutionalised corruption and electricity sector "problem-solving" in Ghana and Kenya. (March 2021) - Boamah, Festus; Williams, David Aled; Afful, Joana
Abstract: The persistence of corruption amid intensified anti-corruption initiatives suggests that entitlement notions underpinning involvement in corrupt practices deserve greater attention. Recent evidence from Africa's energy sector emphasises the functionality of corruption as an unsanctioned remediation response to (perceived) entrenched energy injustices. These insights are absent from recent corruption and energy justice scholarship. In Kenya, uneven spatial distribution of electrical grids, red tape in grid connections, 'unjust' electricity billing systems, and lower energy output of decentralised solar PV systems compelled certain energy users to employ surreptitious strategies to gain or expedite electrical grid access. Lackadaisical enforcement of net metering tariff regulations in Ghana has denied customers entitlements to electricity credits to mitigate against 'unjust' tariffs. Meanwhile, Ghana's main electricity distributor (ECG) continues to bill net-metered customers to compensate for (potential) unbridled tariff defaulting. Some disgruntled customers deliberately defaulted on tariff payments to 'compensate' themselves until ECG threatened to disconnect them from the grid. This article presents survey evidence from Ghana and Kenya showing why energy users and electricity providers justify adherence to 'tit-for-tat' norms and other 'binding precedents' which contravene the law. We argue that energy injustice and corruption are intrinsic to the 'electrification regimes' of both countries, with blatant violations of the law both constraining and enabling energy access. The predominantly Western-framed energy justice scholarship may benefit from a more critical understanding of the relationships between legality and necessity in non-Western energy sectors.